2011
DOI: 10.24908/pceea.v0i0.3984
|View full text |Cite
|
Sign up to set email alerts
|

Development of Anatomically Correct Mock-Ups of the Aorta for Piv Investigations

Abstract: Cardiovascular diseases are the leading cause of morbidity and mortality in Canada and other western countries. In that context, understanding the mechanics involved in the aorta can lead to better comprehension of the interaction of blood flow and wall mechanics in normal and pathologic conditions. In this work, we present the methodologies to create physical models of the aorta for flow visualization purposes in order to assess the effects of compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…There are several clinical trials focused on the wavepropagation phenomenon [35] and experimental studies of flow fields in low α regimes through compliant models [36] - [38], but there are few ex-vivo experimental studies that take into account the effects of aortic compliance on the flow fields in a near-physiological regime.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…There are several clinical trials focused on the wavepropagation phenomenon [35] and experimental studies of flow fields in low α regimes through compliant models [36] - [38], but there are few ex-vivo experimental studies that take into account the effects of aortic compliance on the flow fields in a near-physiological regime.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…There have been several clinical investigations into wave propagation effects in-vivo [47], and experimental investigations into flow fields through compliant phantoms in low α regimes [48][49][50], but, to the authors' knowledge, there has been little experimental investigation into controlled changes in aortic compliance within a physiological range in an ex-vivo environment. There has been a great deal of research into understanding velocity distributions through compliant phantoms using PIV or particle tracking velocimetry (PTV) in cardiovascular flow regimes [38,48,49,51], including the effect of certain pathophysiology such as stenosis [52,53], in compliant pulsatile flow regimes through the use of stereo-PIV and time-resolved PIV. However, to the authors' knowledge, there remains limited understanding of the effect of physiologically relevant aortic compliant response on downstream velocity fields and pump performance.…”
Section: Plos Onementioning
confidence: 99%
“…The compliant response of the aorta has a significant impact on wave propagation effects in-vivo and therefore is widely recognized as being a clinically important marker for overall cardiovascular health [ 43 46 ]. There have been several clinical investigations into wave propagation effects in-vivo [ 47 ], and experimental investigations into flow fields through compliant phantoms in low α regimes [ 48 50 ], but, to the authors’ knowledge, there has been little experimental investigation into controlled changes in aortic compliance within a physiological range in an ex-vivo environment. There has been a great deal of research into understanding velocity distributions through compliant phantoms using PIV or particle tracking velocimetry (PTV) in cardiovascular flow regimes [ 38 , 48 , 49 , 51 ], including the effect of certain pathophysiology such as stenosis [ 52 , 53 ], in compliant pulsatile flow regimes through the use of stereo-PIV and time-resolved PIV.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Clough et al (2012) reported the presence of helical flows at different locations in the false lumen by examining images acquired with phasecontrast magnetic resonance imaging (PC-MRI) and related these helical flows to the aortic expansion rate. More recently, a few research groups are employing laser diagnostic methods to explore the haemodynamics in higher spatial and temporal resolution, using primarily particle image velocimetry (PIV) (Yip et al, 2004;Salameh et al, 2017Salameh et al, , 2019Moravia et al, 2019) and stereo-particle image velocimetry (s-PIV) (Fernandes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%